A double-edged sword: Amylostereum areolatum odors attract both Sirex noctilio (Hymenoptera: Siricidae) and its parasitoid, Ibalia leucospoides. (December 2021) - Faal, Hajar; Cha, Dong H.; Hajek, Ann E.; Teale, Stephen A.
Abstract: The Eurasian woodwasp, Sirex noctilio, is an invasive pest of pines in temperate regions of the Southern Hemisphere, and has been introduced to North America. A parasitoid, Ibalia leucospoides, has been broadly employed for biological control of this pest. Volatiles emitted from the fungal symbiont of S. noctilio, Amylostereum areolatum, are reliable cues for S. noctilio and I. leucospoides females to optimize their foraging behavior (host location and host habitat finding) in a chemically complex environment. The headspace volatiles of A. areolatum, were analyzed using coupled gas chromatography-mass spectrometry (GC-MS) and GC-electroantennographic detection (GC-EAD) for both S. noctilio and I. leucospoides females. Analyses revealed that both species could detect several fungal volatiles. In olfactometer bioassays, S. noctilio females were attracted to a 4-component blend of 6-methyl-5-hepten-2-one, trans-3-hexenyl acetate, linalool, and geraniol, while the addition of ρ-anisaldehyde to the blend was necessary for attraction of I. leucospoides females. The results of trap catches in field experiments confirmed that these fungal volatiles in combination with host tree volatiles are attractive to both species, although the release rate of the fungal volatiles is important. These volatiles can serve as a basis for the development of improved lures for both species.